HIPERTENSAO ARTERIAL EM PACIENTES OBESOS COM HIPERTROFIA CARDIACA. EFEITOS DO CAPTOPRIL SOBRE A SENSIBILIDADE A INSULINA E HORMONIO DE CRESCIMENTO - Velasco-Conejo, I. F. [UNESP]; Martin, Luis Cuadrado [UNESP]; Brandao-Neto, J. [UNESP]; Marchioli, M. [UNESP]; De Barros e Silva, M. [UNESP]; De Cassia Athanazio-Heliodoro, R. [UNESP]; Da Silva Franco, R. J. [UNESP] (My University, 1995)
Purpose. To evaluate the effects of captopril (Cpt) on carbohydrate metabolism and growth hormone (GH) in adults hypertensive obese patients with normal (NGT) or impaired (IGT) glucose tolerance and left ventricular hypertrophy. Methods. Ten patients (53 ± 8 years), 8 women and 2 men, white, body mass index (BMI) ≥ 26 kg/m2, left ventricular mass index (LVMI) > 135 g/m2 in man and > 110 g/m2 in woman, with diastolic blood pressure (DBP) 95-115 mmHg after 3 weeks of placebo, were identified by oral glucose tolerance test (OGTT-75 g) as either with NGT or IGT, and treated with Cpt 25 mg t.i.d. for 8 weeks. At the 8 weeks, dosage was increased to 50 mg b.i.d. if DBP > 90 mmHg or the decrease of the DBP < 10%, during the next 8 weeks. OGTT and clonidine tests (0,04 mg/kg) with determinations, every 30 minutes of glucose, insulin, and GH during 2 hours, were performed. Results. Cpt lowered SBP and DBP in the NGT group and IGT group. The LVMI and the left ventricular mass (LVM) decreased in the IGT group with no significant change in the NGT group. Cpt promoted in the IGT group decrease in the area under the curve (AUC) of glucose, and AUC of insulin, with increase of the AUC of the percent of the β cell function, AUC of HC, and insulin sensitivity index with no significantly change in the NGT group. Conclusion. Adults hypertensive obese patients with IGT had decreased significantly in mean fasting level of GH concentrations compared to age, race, and BMI matched hypertensive patients with NGT. Treatment with Cpt induced a significant increased of the GH, with improvement of the metabolism in patients with IGT.
Hypertension in obese patients with cardiac hypertrophy. Effects of captopril in the insulin sensitivity and growth hormone
Keywords: captopril; glucose tolerance; growth hormone; insulin; antihypertensive agent; lipid; adult; blood pressure; carbohydrate metabolism; clinical article; clinical trial; female; heart hypertrophy; heart left ventricle hypertrophy; human; hypertension; insulin sensitivity; male; obesity; aged; blood; glucose blood level; glucose intolerance; glucose tolerance test; insulin resistance; time; Adult; Aged; Antihypertensive Agents; Blood Glucose; Captopril; English Abstract; Female; Glucose Intolerance; Glucose Tolerance Test; Growth Hormone; Human; Hypertension; Hypertrophy, Left Ventricular; Insulin; Insulin Resistance; Lipids; Male; Middle Age; Obesity; Support, Non-U.S. Gov't; Time Factors